The Importance of Diagnosing Meconium Aspiration and Perinatal Deaths - Gülmen, Mete Korkut; Salaçin, Serpil (The Bulletin of Legal Medicine, 1996)
Turkish manner of criminal code law describes the questions that should raise in a case of criminal perinatal death. In this paper, a case of perinatal death due to meconium aspiration discussed regarding the problems in those cases. Key words: Perinatal Deaths, Meconium Aspiration, Autopsy, Morphology.